Ocular myasthenia - Zakaravičiūtė, J.; Šerelytė, M. (Neurologijos seminarai, 2022)
Myasthenia gravis is a chronic autoimmune neuromuscular disorder typically presenting with variable skeletal muscle fatigue. The most prevalent initial manifestation of myasthenia is ocular myasthenia. Approximately 50% of all myasthenia cases begin with the weakening of the eye muscles that generally presents as diplopia and/or ptosis. However, about 60% of these cases progress to a generalized type within the first 2 years. The diagnosis of ocular myasthenia is often difficult but is collectively confirmed by clinical evaluation and laboratory results. Clinical manifestations, diagnostic approach, relevance, and therapeutic options are discussed in this article.